Neoadjuvant chemotherapy in pregnant patients with cervical cancer: a Latin-American multicenter study - Lopez, A (2021)
Objective: To describe oncologic and obstetric outcomes in patients diagnosed with cervical cancer during pregnancy who had a successful delivery after neoadjuvant chemotherapy.Methods: A multicenter retrospective review was conducted in 12 institutions from six Latin American countries, between January 2007 and December 2018. Data collected included clinical characteristics, neoadjuvant chemotherapy agents, treatment, obstetric and oncologic outcomes. Results: Thirty-three patients were included. Median age was 34 years (range 31-36). Twenty (60.6%) women were diagnosed at early stage (IB), and 13 (39.4%) with locally advanced stage (IIA-IIIB) according to FIGO 2009 classification. Carboplatin and paclitaxel was the most frequent combination used (60.6%). Partial and complete response rates were 27.3% and 9.1%, respectively. Median gestational age at delivery was 35 weeks (range 34-36). All patients had live births delivered by cesarean section. Obstetric pathology: pre-term labor, placenta percreta or intra-uterine growth restriction, was documented in seven patients (21.2%). Two (6.1%) neonates had low birth weight. Definitive treatment was primary chemo-radiation in 19 (57.6%) patients, radical hysterectomy in 11 (33.3%), abandoned radical hysterectomy with para-aortic lymphadenectomy and ovarian transposition in 1 patient (3.0%), and no further treatment in 2 (6.1%) patients. After a median follow-up of 16.3 months (range 2.0-36.9), 8 (26.7%) patients had recurrent disease. Of these, four (13.3%) died due to disease. Conclusion: Neoadjuvant chemotherapy may be offered to patients wishing to preserve an ongoing pregnancy in order to achieve fetal maturity. Long-term consequences of chemotherapy in the child are yet to be determined.